Information search, integration and personalization : 9th International Workshop, ISIP 2014, Kuala Lumpur, Malaysia, October 9-10, 2014, Revised selected papers /: 9th International Workshop, ISIP 2014, Kuala Lumpur, Malaysia, October 9-10, 2014, Revised selected papers. (2016) - Unknown
No abstract available